HUMAN WEIGHT MEASUREMENT PREDICTION WITH VISUAL IMAGES WITH ARTIFICIAL NEURAL NETWORK ALGORITHM - Basit, Abdul; Subroto, Imam Much Ibnu; Dwi Prasetyowati, Sri Arttini (Journal of Telematics and Informatics, 2020)
Measuring instrument becomes very important to be able to know how much human weight is. Weight information is generally obtained from measurements by body scale. One of other methods to find out a person's weight is by image processing. This study aims to calculate body weight by image processing with the Artificial Neural Network algorithm using back propagation method to detect body weight. The results of testing, analysis, and system accuracy of 97% indicate that the method of calculating body weight is very possible through image processing with various provisions and restrictions.   Key words: Weight, Computer Vision, Artificial Neural Network